DETERMINASI KETEPATAN WAKTU PUBLIKASI LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI PT. BURSA EFEK INDONESIA - Apriada, Kadek; Putra, I Gede Cahyadi; Wulandari, Putu Riska (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2025)
This research aims to determine the factors that influence the timeliness of publication of financial reports in manufacturing companies registered with PT. Indonesia stock exchange. The independent variables in this research include profitability, auditor quality, company size, leverage, managerial ownership. The sample in this research wa 105 samples, which were studied for 3 years. This company was determined using the purposive sampling method. The type of data used is secondary data. The analysis technique used is logistic regression. The research results show that the independent variable profitability has a positive effect on the timeliness of the publication of financial reports, the variables auditor quality, company size, leverage, and managerial ownership have a negative effect on the timeliness of the publication of financial reports.